FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DERMATITIS ATOPIK DI PUSKESMAS BANGKINANG KOTA - Alini Alini (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2018)
The incidence rate of atopic dermatitis has increased 2-3 times in recent decades, and has become a health problem in some developing countries. In 2006 in Indonesia found as many as 403,270 cases of dermatitis with prevalence 3.91%. Atopic dermatitis is an allergic disease that is often believed to be genetic or hereditary and often occurs in families whose members also have asthma disorders. This study aims to determine the factors associated with the incidence of atopic dermatitis in Puskesmas Bangkinang Kota 2015. Research design used is a descriptive analytics with cross sectional design. The population in this study was all patients with atopic dermatitis with the number of samples of 30 people, using the technique of acidental sampling. measuring tool that dugunkan in the form of questionnaires, data analysis used is univariat and bivariate. The result of bivariate analysis showed that there was a significant correlation between hereditary factor and the occurrence of atopic dermatitis (p value 0.016), there was a significant association between food allergy with atopic dermatitis occurrence (p value 0,005), there was significant relation between environment and occurrence of atopic dermatitis p value 0,003), there is no significant correlation between irritant with incidence of atopic dermatitis (p value 0,169). It is expected that health workers can provide information on the factors that cause atopic dermatitis to avoid triggering factors and aggravate the atopic dermatitis